2019
DOI: 10.1107/s160057751801648x
|View full text |Cite
|
Sign up to set email alerts
|

In situ high-temperature EXAFS measurements on radioactive and air-sensitive molten salt materials

Abstract: An experimental set-up and specific sample containment allowing high-temperature in situ EXAFS measurements of radioactive, air-sensitive and corrosive fluoride salts is described. First results are reported and compared with molecular dynamics simulations of the highly disordered liquid salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The suitability of the experimental set-up was originally tested on ThF 4 (cr) at room temperature as reported in ref. 9. In a later campaign the EXAFS spectrum of UF 4 (cr) was collected and is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The suitability of the experimental set-up was originally tested on ThF 4 (cr) at room temperature as reported in ref. 9. In a later campaign the EXAFS spectrum of UF 4 (cr) was collected and is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MD has demonstrated already in numerous studies to be a strikingly valuable tool in its own right for calculating the thermo-physical and thermo-chemical properties of molten salts. [14][15][16][17] In other works, our group has presented EXAFS data of the LiF-ThF 4 , 9 LiF-UF 4 (submitted), and NaF-ThF 4 9 systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 †). X-ray absorption spectroscopy (XAS) is a powerful tool to investigate metal ion speciation, [15][16][17][18] but provides reliable information only about the rst coordination sphere, and recent XAS experiments were unable to determine the local structure of Cr 3+ in a KCl-MgCl 2 molten salt mixture at the high temperatures (>973 K) 19 that are relevant to technological processes in CSP and MSR applications. The accurate identication and understanding of coordination environments and dynamic structural behaviour of chromium species could provide useful insights into the processes of corrosion and transport in molten salts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Toth et al showed the presence of [ThF 8 ] 4and [ThF 7 ] 3species in LiF-NaF-ThF 4 mixture [15]. More recently, Bessada et al [16] followed by Smith et al [17], developed a new set-up and a sample containment cell for measuring local structure of radioactive molten fluorides AF-ThF 4 (A + = K + , Li + ) by extended X-ray absorption fine structure (EXAFS) at the L 3 threshold of the thorium. This spectroscopic technique, sensitive to the local environment around a given element, is well adapted to obtain qualitative and quantitative information on the first solvation shell of heavy cations such as thorium.…”
Section: Introductionmentioning
confidence: 99%